A new class of Bernstein-type operators obtained by iteration - PĂLTĂNEA, Radu; SMUC, Mihaela (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
A new class of Bernstein-type operators are obtained by applying an iterative method of modifications starting from the Bernstein operators. These operators have good properties of approximation of functions and of their derivatives. Mathematics Subject Classification (2010): 41A36, 41A10, 41A25. Received 23 February 2022; Accepted 22 September 2022.